Dispositivos emisores de luz basados en compuestos semiconductores orgánicos: una revisión aplicada a emisores rojos - Ardila-Vargas, Ángel-Miguel; Méndez-Merchán, Germán-Anibal; Burgos-Castro, Valeria (Revista Científica, 2022)
A review of the current state of organic light-emitting devices (OLED) is presented, with an emphasis on those that emit in the red band. To understand the operation of this type of device, the different architectures used and the emission mechanisms of these optoelectronic devices by fluorescent and phosphorescent radiation are shown. For the case of red emitters, examples with the two most commonly used types of materials are presented: DJCTB for fluorescence and Ir(piq)2(acac) for phosphorescence. Although the architectures and mechanisms herein reviewed apply to red emitters, they can also be extended to emitters throughout the visible range.